2021
DOI: 10.3390/ijms222010921
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Localization: A Key to Differential Energy Regulation

Abstract: As the central node between nutrition signaling input and the metabolic pathway, AMP-activated protein kinase (AMPK) is tightly regulated to maintain energy homeostasis. Subcellular compartmentalization of AMPK is one of the critical regulations that enables AMPK to access proper targets and generate appropriate responses to specific perturbations and different levels of stress. One of the characterized localization mechanisms is RanGTPase-driven CRM1 that recognizes the nuclear export sequence (NES) on the α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Once internalized in host cells, phosphorylation of AMPKα is reduced and a balance between energy producing catabolism and biomass synthesizing anabolism is achieved, enabling robust proliferation of the parasites. eukaryotes, AMPK shuttles between the nucleus and cytoplasm in a Ran GTPase-dependent manner and such shuttling can be modulated by stresses 41 . Our results showed that phosphorylation and activation of Toxoplasma AMPK was drastically increased upon the release of intracellular parasites into extracellular environments.…”
Section: Discussionmentioning
confidence: 99%
“…Once internalized in host cells, phosphorylation of AMPKα is reduced and a balance between energy producing catabolism and biomass synthesizing anabolism is achieved, enabling robust proliferation of the parasites. eukaryotes, AMPK shuttles between the nucleus and cytoplasm in a Ran GTPase-dependent manner and such shuttling can be modulated by stresses 41 . Our results showed that phosphorylation and activation of Toxoplasma AMPK was drastically increased upon the release of intracellular parasites into extracellular environments.…”
Section: Discussionmentioning
confidence: 99%
“…29 It could be activated by many factors, like oxidant, circadian rhythm, heat shock, starvation, and hypoxia. 30 Several studies revealed that AMPK could promote the initiation of autophagy via activating Ulk1 through phosphorylating Ulk1 Ser317 and Ser777. 31,32 Besides, AMPK could directly phospho-rylate Beclin-1, which is the component of Ulk1 downstream complex during the process of autophagosome formation.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPK is a highly conserved αβγ heterotrimeric serine‐threonine kinase that could regulate cellular energy homeostasis via sensing the concentrations of AMP 29 . It could be activated by many factors, like oxidant, circadian rhythm, heat shock, starvation, and hypoxia 30 . Several studies revealed that AMPK could promote the initiation of autophagy via activating Ulk1 through phosphorylating Ulk1 Ser317 and Ser777 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, AMPK induces catabolic pathways to produce energy and prevents anabolic pathways, such as lipid and protein synthesis, to save energy ( Wanet et al, 2015 ). On the other hand, considerable evidence shows that AMPK regulates cell fate, including controlling stem cell pluripotency and differentiation ( Afinanisa, Cho & Seong, 2021 ; Fernandez-Veledo et al., 2013 ; Liu et al, 2021 ). In this study, CCCP-treated hDPSCs exhibited an elevated level of p-AMPK, showing that the energy sensor AMPK was involved in the process of metabolism that influenced differentiation.…”
Section: Discussionmentioning
confidence: 99%